KESIAPAN DAN TANTANGAN IMPLEMENTASI MODEL CHALLENGE-BASED LEARNING DALAM PEMBELAJARAN IPAS KELAS IV SEKOLAH DASAR - Hawa, Siti; Abidin, Yunus; Undayasari, Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
21st century learning demands the application of a learning model that is able to integrate knowledge, skills, and attitudes through real context. One relevant model is Challenge-Based Learning (CBL). This study aims to describe the readiness and challenges of CBL implementation in class IV science learning in elementary schools. The research method used is a qualitative approach with a case study design. Which involved grade IV teachers and students in one elementary school as research subjects. Data were collected through learning observations, semi-structured interviews with teachers, targeted group discussions with students, and analysis of learning documents. The data analysis process follows an interactive model with the stages of data reduction, presentation and finally conclusion drawn. The validity of the validity of the data is complemented by triangulation of sources and techniques. The results of the study show that teachers show a positive attitude of readiness supported by the results of students' tests, but pedagogical and technical readiness is still limited. The main challenges include limited learning time, differences in students' abilities, limited supporting facilities, and difficulties in designing authentic assessments. This study confirms that the implementation of CBL in primary schools requires support for teacher training and sustainable school policies.